Uso de recursos y sistemas de gestión administrativa en Oficina Desconcentrada Sechura del Organismo Nacional de Sanidad Pesquera 2016-2020 - Pazo Nunura, Carlos Alexander (2021)
The National Organism for Fisheries Health is a public institution that is attached to the ministry of production, within its functions, there are professionals who are responsible for carrying out trips to the sea in the bay of sechura, to extract samples of seawater and product, which are analyzed in their own laboratories located in Sechura-Piura and Ventanilla-Callao, thus certifying the safety of the product for its consumption, the national organism for fisheries health uses administrative management systems that contribute to the control and monitoring of internal and external procedures, thus allowing a better performance in administrative functions, within the national agency for fisheries health the performance of the powers and functions of the administrative assistant is framed by procedures and directives that must be complied with and coordinated with the head of the sechura decentralized office and also with the administration office, since authorization is required to proceed with administrative management.